Pencapaian Keluarga Sakinah melalui Pemberdayaan Ekonomi di Desa Buddagan Kecamatan Pademawu - Erie Hariyanto; Maimun Maimun; Ainurrahman Hidayat (IAIN Madura, 2020)
The number of divorce cases in Indonesia, child abuse, violence, and criminal acts in the household are proof that in realizing the Sakinah family requires the involvement of several parties; parents, the Religious Affairs, and the village government. This community service theme has a correlation with the District Office of Religious Affairs (KUA) in Pademawu District, Pamekasan Regency. The functions and duties were to deal with quite complex issues concerning all religious matters including marriage, divorce, divorce, reconciliation.